27=b(b-6)

Simple and best practice solution for 27=b(b-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=b(b-6) equation:



27=b(b-6)
We move all terms to the left:
27-(b(b-6))=0
We calculate terms in parentheses: -(b(b-6)), so:
b(b-6)
We multiply parentheses
b^2-6b
Back to the equation:
-(b^2-6b)
We get rid of parentheses
-b^2+6b+27=0
We add all the numbers together, and all the variables
-1b^2+6b+27=0
a = -1; b = 6; c = +27;
Δ = b2-4ac
Δ = 62-4·(-1)·27
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{144}=12$
$b_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-12}{2*-1}=\frac{-18}{-2} =+9 $
$b_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+12}{2*-1}=\frac{6}{-2} =-3 $

See similar equations:

| 15x=14x-7= | | 12=z-28 | | 3x+1=2x-4= | | -16d+8=-15d | | (d-7)(d+4/3)=0 | | 88=(2t*3)+4 | | 3(2y-8)+20=4y | | 12^2-6x=0 | | -2(7-w)=4(w+1) | | b/3+b/3+b=180 | | 1+5s=17+4s | | 2(4-y)=40 | | 7(y+5)=-9y-29 | | (62-5x)=133 | | .6x-4+.2x=28 | | x=10+4x5 | | x-6=17+13 | | -11.29+18.1p+4.05=14.3p-17.12 | | (7x+6)=78 | | (5x+21)=120 | | (8x-9)=158 | | x6=33 | | 4-((2x-3)=3 | | 19=8=y | | 2x-15)+(2x+10)+(2x+5)=180 | | 19r-4r+18=13r-18 | | q+444/31=27 | | 15x-12=7x+4 | | -20c=10-19c | | 1/3x+1/5x+56=x | | 3.2+x/3=-4.3 | | -18-6z=-12z |

Equations solver categories